2017
DOI: 10.1007/s40617-017-0175-y
|View full text |Cite
|
Sign up to set email alerts
|

An Abbreviated Evaluation of the Efficiency of Listener and Tact Instruction for Children with Autism

Abstract: We assessed the efficiency of tact and listener training for eight participants with autism spectrum disorder. Tact and listener probes were conducted in baseline for all target sets, and then tact training was initiated with one and listener training with another. Following mastery of one set, tact and listener probes were conducted with only the sets assigned to the same modality of training (i.e., sets 1, 3, and 5 for tact; sets 2, 4, and 6 for listener). Training and probes were repeated for all sets. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Following the selection response and possible covert tact, the instructor provided reinforcement in the form of a token, which would only further strengthen the future emission of both responses. This simultaneous reinforcement for both tact and listener responding has been thoroughly outlined by Horne and Lowe () and Miguel (; ), with many experimental studies supporting the viability of this conceptualization (e.g., Delfs et al, ; Frampton, Robinson, Conine, & Delfs, ; Kobari‐Wright & Miguel, ; Sprinkle & Miguel, ).…”
Section: Discussionmentioning
confidence: 73%
“…Following the selection response and possible covert tact, the instructor provided reinforcement in the form of a token, which would only further strengthen the future emission of both responses. This simultaneous reinforcement for both tact and listener responding has been thoroughly outlined by Horne and Lowe () and Miguel (; ), with many experimental studies supporting the viability of this conceptualization (e.g., Delfs et al, ; Frampton, Robinson, Conine, & Delfs, ; Kobari‐Wright & Miguel, ; Sprinkle & Miguel, ).…”
Section: Discussionmentioning
confidence: 73%
“…All five studies compared speaker training to listener training, and one also compared a mixed training format to the other two (Bao, Sweatt, Lechago, & Antal, ). Three studies compared the relative efficiency of tact training to listener training (Delfs, Conine, Frampton, Shillingsburg, & Robinson, ; Frampton, Robinson, Conine, & Delfs, ; Sprinkle & Miguel, ). In all three studies, tact training involved showing the participant a visual discriminative stimulus (S D ) along with a vocal S D (e.g., “What is it?”).…”
Section: Resultsmentioning
confidence: 99%
“…Each study measured the emergence of targets in one operant class following training in the other operant class (e.g., measuring listener responding after speaker training). Thus, we will discuss the results of each study in terms of the targets that emerged following training (see Frampton et al, for a discussion of using multiple DVs to evaluate relative efficiency). Speaker training was more efficient than listener training for 16 of 21 participants (i.e., more listener responses emerged following speaker training than speaker responses emerged following listener training).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study conducted by Delfs, Conine, Frampton, Shillingsburg, and Robinson () showed that teaching young children with autism spectrum disorder to tact pictures of objects, states, and people (e.g., pilot) more reliably resulted in emergent listener responding than vice versa for most participants. This finding has been demonstrated across different populations, stimuli, and slightly different training methods (e.g., Frampton, Robinson, Conine, & Delfs, ; Horne, Lowe, & Randle, ; Kobari‐Wright & Miguel, ; Lee, Miguel, Darcey, & Jennings, ; Lowe, Horne, Harris, & Randle, ; Miguel & Kobari‐Wright, ; Sprinkle & Miguel, ; Wynn & Smith, ). Researchers also have demonstrated that acquisition of the naming relation (Horne & Lowe, ) may result in emergent listener responding, tact responding, and stimulus class formation (categorization skills) for some young children (e.g., Miguel & Kobari‐Wright, ; Miguel, Petursdottir, Carr, & Michael, ).…”
mentioning
confidence: 81%